Evaluasi Metode Penilaian Perkembangan Siswa dan Pendidikan Karakter dalam Kurikulum Merdeka Pada Sekolah Dasar - Armini, Ni Kadek (Jayapangus Press, 2024)
A number of previous studies by education experts have discussed character education and developmental assessment at the primary school level. However, studies that explicitly examine the integration of these two aspects in the Merdeka Curriculum are limited. Most previous research has focused more on the pre-existing curriculum, with different approaches to assessment and character education. This study aims to evaluate methods of assessing student growth and character education in the implementation of Merdeka Curriculum at the elementary school level. This research uses a qualitative method, with a literature review approach. The results show an emphasis on students' individual development and potential in the context of education. This approach also includes aspects of character education both in the teaching and learning process and in assessment, where character education is integrated not only in certain subjects but also through daily activities and school interactions. Merdeka Curriculum adopts a holistic approach to assessment that supports students' personal growth. Character education is an essential component in this curriculum to foster positive values and student behavior in everyday life. However, there are challenges such as the need for teacher training for effective and consistent integration of character education in the learning and assessment process.